EMPLOYMENT POSSIBILITIES IN RURAL AREAS OF VOJVODINA - Šumljanac Šećerov, Mirjana; Matijević, Vladimir; Kos, Darinka (Economics of Agriculture, 2007)
Through an insight into the needs for exploitation of possible and existing resources, both human and material, as well as into their present condition, a possibility for development of employment policy can be observed. Bearing in mind the quality and state of the land and the developed system of economic potentials, food production and processing become an imperative of the future development of the whole region, especially its rural areas. The capacities of specialists registered with the National Employment Service in Vojvodina have to become a significant development factor, so it is necessary to introduce them into the world of work and put them in proper use. Therefore all relevant factors must put a joint and coordinated effort to increase participation of the National Employment Service in the labour market with the purpose of improving competitiveness and employability of competent workforce, which can be achieved through implementation of active employment policy measures. The end result of this will be a decrease in unemployment rates and alleviation of the social exclusion of risk groups, facilitating an employment increase, consistent with the requirements of the National Employment Strategy.